2016
DOI: 10.1113/jp272287
|View full text |Cite
|
Sign up to set email alerts
|

Phrenic motor outputs in response to bronchopulmonary C‐fibre activation following chronic cervical spinal cord injury

Abstract: Cervical spinal injury interrupts bulbospinal pathways and results in cessation of phrenic bursting ipsilateral to the lesion. The ipsilateral phrenic activity can partially recover over weeks to months following injury due to the activation of latent crossed spinal pathways and exhibits a greater capacity to increase activity during respiratory challenges than the contralateral phrenic nerve. However, whether the bilateral phrenic nerves demonstrate differential responses to respiratory inhibitory inputs is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…38 Moreover, prolongation of the expiratory duration during activation of pulmonary stretch receptors and bronchopulmonary C-fibers was also attenuated in cervical spinal injured rats. 9,39-41 These data imply that cervical SCI may restrict the alteration of respiratory frequency in response to respiratory stimuli. Interestingly, the respiratory frequency of contused animals, but not sham surgery animals, remained higher than baseline at 5 minutes after first hypoxic treatment, suggesting offset STP of respiratory frequency was evident in contused animals.…”
Section: Discussionmentioning
confidence: 86%
“…38 Moreover, prolongation of the expiratory duration during activation of pulmonary stretch receptors and bronchopulmonary C-fibers was also attenuated in cervical spinal injured rats. 9,39-41 These data imply that cervical SCI may restrict the alteration of respiratory frequency in response to respiratory stimuli. Interestingly, the respiratory frequency of contused animals, but not sham surgery animals, remained higher than baseline at 5 minutes after first hypoxic treatment, suggesting offset STP of respiratory frequency was evident in contused animals.…”
Section: Discussionmentioning
confidence: 86%
“…First, the cervical spinal contusion directly damaged the bulbospinal respiratory pathways (27,28); thus there were fewer phrenic motoneurons still receiving projections from the premotor neuron in the brainstem when the respiratory drives were lower during sleep. Second, the excitability and phenotype of phrenic motoneurons were changed following cervical spinal cord injury (23,26,32), which may further interfere with the effect of sleep-induced changes in the respiratory drives on the phrenic motor output. Third, our recent report indicated that upper airway function was also impacted by cervical spinal cord injury (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a rapid shallow breathing pattern was observed in rats with high-and midcervical spinal cord injuries (29). The phrenic electroneurogram and diaphragm electromyogram were significantly impacted by cervical spinal cord injury (18,23,28,55,58,59). These animal models were also used to evaluate the effectiveness of several potential therapeutic strategies for improving respiratory function, such as cellular transplantation, pharmacological administration, neurorehabilitative training, and magnetic/electrical stimulation (13,16,25,27,36,49,57).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alteration of phrenic motoneuronal excitability following cervical spinal cord injury may also potentiate the effect of dAIH and/or 5-HT7 receptor antagonist. [42][43][44] However, since our injury leads to a phrenic motoneuronal loss on the injured side, 10,11 we cannot rule out that the phrenic neuroplasticity that sustains the tidal volume increase in response to dAIH could happen into the phrenic motoneurons in the intact side, 45 as well as other respiratory-associated muscles such as the intercostals. 21,46,47 In addition, supraspinal respiratory-related nucleus and/or spinal interneurons may be also involved in modulating the tidal volume in our current experimental model.…”
Section: The Potential Mechanism Underlying the Effect Of 5-ht7 Recepmentioning
confidence: 93%